1994
DOI: 10.1016/s0969-2126(00)00012-5
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of chloroplast cytochrome freveals a novel cytochrome fold and unexpected heme ligation

Abstract: The first atomic structure of a subunit of either the cytochrome b6f complex or of the related cytochrome bc1 complex has been obtained. The structure of cytochrome f allows prediction of the approximate docking site of plastocyanin and should allow systematic studies of the mechanism of intra- and inter-protein electron transfer between the cytochrome heme and plastocyanin copper, which are approximately isopotential. The unprecedented axial heme iron ligand also provides information on the sequence of events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
309
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(323 citation statements)
references
References 46 publications
(50 reference statements)
14
309
0
Order By: Relevance
“…The spectroscopic results presented here for the cytochrome [24], cytochrome f (His/N-terminal amine) [25], and the butylb560 of bovine SQR complement those obtained previously for amine adduct ofleghemoglobin [19]. Alkaline cytochrome c has the cytochrome b components of B. subtilis and E. coli SQR 2cx = 1480 nm with Ae = 420 M -~ "cm -I (4.2 K and 5 T) [26], [16,17].…”
Section: K and 5 T) In Sqr And Is Broadened And Shifted To 1535supporting
confidence: 81%
“…The spectroscopic results presented here for the cytochrome [24], cytochrome f (His/N-terminal amine) [25], and the butylb560 of bovine SQR complement those obtained previously for amine adduct ofleghemoglobin [19]. Alkaline cytochrome c has the cytochrome b components of B. subtilis and E. coli SQR 2cx = 1480 nm with Ae = 420 M -~ "cm -I (4.2 K and 5 T) [26], [16,17].…”
Section: K and 5 T) In Sqr And Is Broadened And Shifted To 1535supporting
confidence: 81%
“…Modifications of the Hinge and Vise that Affect TurnoVer of the bc 1 Complex. Several lines of evidence have suggested that modification of the vise region or hinge might affect reactions at the Q o site.…”
Section: Mobility and Binding Of The Isp: Complementary Functional Asmentioning
confidence: 99%
“…The ubihydroquinone:cytochrome c oxidoreductase (bc 1 complex) 1 (E.C. 1.10.2.2) and the related b 6 f complex of oxygenic photosynthesis are central components of the major electron-transfer chains that carry the energy flux of the biosphere.…”
mentioning
confidence: 99%
“…In addition, the positions of the heme domains, in particular the distances between the heme-irons of each monomer and the orientations of the cyt c 1 and cyt f heme planes are also dissimilar, with the former being almost perpendicular to the membrane, and the latter at a 25-30° angle from it ( (Kurisu et al 2003;Stroebel et al 2003)). Finally, although one axial ligand of the heme is His in both cyts, the other axial ligand is Met in cyt c 1 while the NH 2 group of the N-terminus plays this role in cyt f ( (Martinez et al 1994)). …”
mentioning
confidence: 99%